2013
DOI: 10.1186/1471-2458-13-854
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function, chronic respiratory symptoms, and health-related quality of life among adults in the United States – National Health and Nutrition Examination Survey 2007–2010

Abstract: BackgroundWe examined the association of impaired lung function and respiratory symptoms with measures of health status and health-related quality of life (HRQOL) among US adults.MethodsThe sample included 5139 participants aged 40–79 years in the National Health and Nutrition Examination Survey 2007–2010 who underwent spirometric testing and responded to questions about respiratory symptoms, health status, and number of physically unhealthy, mentally unhealthy, or activity limitation days in the prior 30 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 24 publications
4
32
2
Order By: Relevance
“…Likewise, in a study by Kim et al , 5 28% of patients had preoperative FVC less than 65%. [26][27][28] Progressive scoliosis until adulthood is a risk factor for impaired PF. [23][24][25] Young patients with scoliosis with FVC less than 50% have an alleviated prognosis for respiratory failure in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in a study by Kim et al , 5 28% of patients had preoperative FVC less than 65%. [26][27][28] Progressive scoliosis until adulthood is a risk factor for impaired PF. [23][24][25] Young patients with scoliosis with FVC less than 50% have an alleviated prognosis for respiratory failure in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years multiple population-based studies have shown that a significant proportion of the general adult population has a restrictive pattern on spirometry, characterised by reduced levels of forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC), and normal FEV1/FVC ratio [1][2][3][4]. Although the determinants and biological bases of this restrictive pattern remain largely unknown, subjects with spirometric restriction have been shown to be more likely to have cough and phlegm, shortness of breath with wheezing and dyspnoea [3,[5][6][7], and suffer from and die of a number of comorbidities, including coronary heart disease, hypertension, metabolic syndrome and diabetes [2,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Similar data have been reported from other countries 3, 4 . Apart from the morbidity burden, lung diseases are also associated with poor quality of life and repeated hospitalizations and incur higher health care costs 48 .…”
mentioning
confidence: 99%